Public administration in the new reality - Baimenov, Alikhan; Liverakos, Panos
This book combines academic insights and practitioners’ experience from nineteen countries around the world, and it explores public administration systems capacity in predicting, facing, and reacting to, as well as operating in, the new reality. A reality characterised by considerable levels of volatility, uncertainty, complexity, and ambiguity; all amid rising geo-political tensions, climate change, digital transformation, aging populations, urbanisation, migration, and environmental degradation. These complex and intertwined policy issues put to test contemporary governance structures and current organisational arrangements for public administration systems, as well as the existing competencies and skills of public administrators. Thus, this book explores what public administration systems must do to keep up with the immense changes taking place around us and adapt to the new reality, as well as possess the capacity to forecast, to react and to learn from all past crises and manage competing and conflicting values as well.